New Estimates of Government Net Capital Stocks for 22 OECD Countries 1960-2001 - Kamps, Christophe (International Monetary Fund, 2004)
The issue of whether government capital is productive has received a great deal of recent attention. Yet empirical analyses of public capital productivity have generally been limited to the official capital stock estimates available in a small sample of countries. Alternatively, many researchers have investigated the output effects of public investment-recognizing that investment may be a poor proxy for the corresponding capital stock. This paper attempts to overcome the data shortage by providing internationally comparable capital stock estimates for 22 Organization for Economic Cooperation and Development (OECD) countries